Peningkatan Kedisiplinan Belajar Siswa Kelas VIII melalui Pembiasaan Shalat Dhuha di MTs Sunan Kalijaga Boyolali Tahun Ajaran 2025/2026 - Maulana, Muhammad Aman; Matori, Matori; Rosidi, Ayep (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the improvement of eighth-grade students’ learning discipline through the habituation of Dhuha prayer at MTs Sunan Kalijaga Boyolali in the 2025/2026 academic year. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The research informants included the principal, Islamic Religious Education teachers, homeroom teachers, and eighth-grade students. The results show that the habituation of Dhuha prayer conducted routinely before the learning process is able to improve students’ learning discipline, particularly in aspects of punctuality, learning readiness, compliance with school regulations, and academic responsibility. The habituation of worship also has an impact on students’ psychological calmness and self-control, thereby supporting a more conducive learning process. The study concludes that the habituation of Dhuha prayer is an effective strategy to improve students’ learning discipline while strengthening religious character based on Islamic education values.